Improvement of the national judicial system in the Republic of Kazakhstan: analysis of innovations and problems - Zhursimbayev, S.K.; Kemali, E.S.; Muratova, A.Zh. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article presents key directions and outcomes of judicial reform in Kazakhstan within the larger context of public governance transformation and consolidation of the rule of law. The purpose of the research was to conduct a systematic analysis of institutional and procedural changes within the judicial system, such as digitalization, introducing a three-tier cassation model, elements of judicial election, reform of disciplinary accountability, as well as strengthening judicial independence judicially. As its object of study was the contemporary Kazakh judiciary, while its subject was mechanisms used for reform, including associated risks as well as prospective developments of said system. This study's methodology draws upon formal legal, comparative legal, historical legal, and systems-based methods of inquiry. As part of their analysis, the authors identify both positive developments as enhanced procedural transparency, greater judicial autonomy, and implementation of digital tools, and persistent structural issues, such as excessive filtering of cassation appeals, limited access to justice in remote regions, and uncertainty within disciplinary procedures. Particular attention is also paid to legal regulation of procedural timeframes as well as any relations between judicial independence and efficiency in disciplinary processes.